Synergistic effect of binary systems of nanostructured MoS2/SiO2 and GO/SiO2 as additives to coconut oil-derived grease: Enhancement of physicochemical and lubrication properties - Rawat S.S.; Harsha A.P.; Khatri O.P. (My University, 2025)
The present work addresses the use of synergistic blends of two different types of nanomaterials (spherical particles and lamellar sheets) as additives for coconut oil-based grease formulation to provide the energy-efficient and sustainable alternative to conventional grease. The spherical SiO2 nanoparticles are separately blended with 2D lamellar sheets of MoS2 and graphene oxide (GO) in variable ratio and probed their synergistic effects for enhancement of physicochemical and lubrication properties. The SiO2 nanoparticles, MoS2, and GO nanosheets are prepared by modified sol–gel, hydrothermal reduction, and Hummer's methods, respectively. The 0.05 wt% nanomaterials blends of MoS2/SiO2 (30:70) and GO/SiO2 (50:50) as optimised doses furnished the maximum reduction in the friction and wear. The combination of rolling friction and low shear properties using the synergistic blend of the spherical nanoparticles (SiO2) and nanosheets (MoS2 and GO) showed significant improvement in tribological properties. The optimised blends of nanoadditives, that is, MoS2/SiO2 and GO/SiO2 conserved the energy by 20% and 19%, respectively. These findings suggest that the use of synergistic blends of variable nanomaterials to vegetable oil-based lubricants can pave a direction for new generation lubricant formulation, where environmental sustainability and energy conservation are on prime importance. © 2021 John Wiley & Sons, Ltd